Framing of the Unified Examination Certificate by Malaysian Ethnic Newspapers - Lam, Kai Chee; Yeo Wei, Ting; Lay Hoon, Ang; Hoe, Foo Terng (Chulalongkorn University., 2022)
Media framing makes an issue salient. This study attempts to determine the frequency of episodic and thematic frames in news about the Unified Examination Certificate issue and identify the framing dimensions and valence used. Textual analysis of the content and headlines was performed on 100 news articles from newspapers of two languages. Results indicate that all the articles were framed episodically, with the “attribution of responsibility” dimension used most frequently, followed by the “human interest” and “conflict” dimensions. Chinese articles tended to use neutral valance, whereas Malay articles mostly used negative valence. These findings provide insights into ethnic politically-influenced and reader-oriented presentations of an issue by different newspapers. Future studies may focus on newspapers using the same language and investigate the framing effects by mainstream and alternative media.